ESOKO Integration with digital financial products as a bundled service to AICCRA Farmers - Nii-Koi, Gordon (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
Esoko Ghana implements an innovative agricultural value chain digitization service called the Digital Farmer Service (DFS) project and in partnership with Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) that leverages mobile and web technologies to develop a super-agent network across several vulnerable farming communities; creating an ecosystem that connects farmers to services by linking them to various actors along the agricultural value chain (input dealers, financial institutions, insurance etc.) using mobile and web technologies. The Field Agents equipped with tablets running Esoko technologies serve as conduits for providing critical services to thousands of smallholders. Since 2005, Esoko has evolved in the field of ICT for agriculture and rural development in Ghana and across Africa. As a social enterprise, our mission is to impact the lives of smallholder farmers and other marginalized people in rural communities. We use mobile technology to make markets more efficient and to enable people at the bottom of the pyramid to gain access to information, products and services that they otherwise are excluded from. Esoko Ghana is pleased to introduce a form of microinsurance called ‘Esoko BanbƆ’ as part of its bundled services to rural folks. Microinsurance is a form of insurance designed for low- and middle- income consumers in emerging markets. The insurance product is usually characterized by small premiums, simple features and benefits tailored to emerging customers’ needs.